“Memorial Constructions”:: Representations of Identity in the Design of the Grand-Pré National Historic Site, 1907-Present - Gagné, Michael (Acadiensis, 2013)
The recent designation of Grand-Pré as a UNESCO world heritage site has led to a new definition of the area based on its “universal” value. The complex history of the site, however, makes the concept of universality problematic. Grand-Pré has been characterized, over the years, by several identities that have been imposed on the landscape and on the monuments and features of the Grand-Pré National Historic Site. Although many historians have emphasized the role of Grand-Pré in Acadian identity formation, this article looks at how the site’s competing identities were both represented and challenged through the design of the park.